Initial Evaluation of Safety and Immunomodulatory Potential of Dietary Supplementation with Mangosteen Pericarp Extract for Sustainable Meat Production in Native Crossbred Chickens - Phruedrada Kaewtui; Chompunut Lumsangkul; Apinya Satsook; Korawan Sringarm; Chaiwat Arjin; Wanaporn Tapingkae; Pimporn Khamtavee; Orranee Srinual; Montri Punyatong; Kiattisak Huanhong; Peerawit Chongrattanameteekul; Natpasit Rattaworapanit; et al. (Life)
The utilization of mangosteen biomass not only solves environmental problems but also raises the value of agricultural waste. The current study aimed to evaluate the potential of mangosteen pericarp extract (MPE) for enhancing the immunity and productivity of Thai native crossbred chickens on-farm. A total of 180 three-week-old chickens were divided into negative control and supplemented groups, with 1000 mg MPE/kg of diet. The safety of MPE was further confirmed by the absence of noticeable differences in mortality and biochemical parameters during the entire study period. The MPE-supplemented group displayed significant differences in the relative transcription levels of IL-10 compared to the basal diet group (p ≤ 0.01). Preslaughter body weight, average daily gain, and carcass weight in the MPE-supplemented group were higher than those in the basal diet group (p ≤ 0.05). Furthermore, MPE supplementation improved meat quality by enhancing the nutritional composition of protein and fat (p ≤ 0.05), as well as improving water-holding capacity, lowering boiling, and lowering grilling losses (p ≤ 0.01). These findings indicate that MPE can be an effective supplement for enhancing flock immunity, growth performance, and meat quality in poultry. This contributes to more sustainable agriculture and food security within agroecosystems.